2014
DOI: 10.1111/clr.12339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platform switching on marginal peri‐implant bone‐level changes. A systematic review and meta‐analysis

Abstract: ObjectiveTo address the focused question, is there an impact of platform switching (PS) on marginal bone level (MBL) changes around endosseous implants compared to implants with platform matching (PM) implant-abutment configurations?Material and methodsA systematic literature search was conducted using electronic databases PubMed, Web of Science, Journals@Ovid Full Text and Embase, manual search for human randomized clinical trials (RCTs) and prospective clinical controlled cohort studies (PCCS) reporting on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 34 publications
(130 reference statements)
6
102
2
6
Order By: Relevance
“…One reached a similar conclusion to this meta-analysis in that the greater the mismatch between the implant platform and the abutment, the greater the bone preservation, 8 while the other suggested that there was significantly less MBL with a platform-switched implant as compared to a platform-matched implant. 9 These two studies corroborate the results from this systematic review and meta-analysis and also inform the reader that we are still awaiting longer-term clinical investigations whereby more definitive conclusions as to the theorised benefits of platform-switching may be drawn.…”
supporting
confidence: 78%
“…One reached a similar conclusion to this meta-analysis in that the greater the mismatch between the implant platform and the abutment, the greater the bone preservation, 8 while the other suggested that there was significantly less MBL with a platform-switched implant as compared to a platform-matched implant. 9 These two studies corroborate the results from this systematic review and meta-analysis and also inform the reader that we are still awaiting longer-term clinical investigations whereby more definitive conclusions as to the theorised benefits of platform-switching may be drawn.…”
supporting
confidence: 78%
“…However, details of the retention type were frequently not present, which cannot eliminate the influence of cement 54 on MBL and PD as possible etiology. In addition, implant‐abutment connection type is also an important factor in MBL 55 , 56 . Nevertheless, these data were not sufficiently clear in some of the included studies.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of PS abutment designs on MBL has been widely investigated; however, the results are controversial, 20 , 39 , 40 and no clear conclusion could be drawn at this point. Although clinical studies and systematic reviews have reported potential beneficial effects, 17 , 20 , 39 multiple studies failed to demonstrate any significant difference if thin mucosa (<2 mm) is present 22 , 41 . Accordingly, Vandeweghe and DeBruyn concluded that PS is effective only when mucosal thickness is enough for establishment of BW 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the concept of PS has been widely studied during the last decade and shows promising results 17–19 . Multiple randomized controlled trials as well as systematic reviews have confirmed its efficacy in maintaining crestal bone 17 , 20 , 21 …”
mentioning
confidence: 99%